Toxic Relationships in Islamic Law - Noor Rizky, Ahya Maulida; Mardia, Nur; Nasrudin, Nasrudin (Medina-te : Jurnal Studi Islam, 2023)
Islam clearly prohibits acts of violence. Toxic relationships are part of violence, whether physical, sexual, or verbal. Therefore, in this research, the author tries to explain toxic relationships from the perspective of Islamic law. This research is a type of literature research whose data sources are articles from journals, books, and documents related to toxic relationship issues. The results of this research show that physical violence is a criminal act (jarimah) and criminal acts against other than the soul in Islamic criminal law. The punishment for perpetrators of crimes other than life is: The main punishment is qishas. Furthermore, sexual violence is also prohibited in Islam because this act does not reflect human values, let alone Islamic values, because it does not contain good relationships (mu'asyarah bi al-ma'ruf). Lastly, verbal or psychological violence in relation to one's partner is the Prophet's prohibition on saying 'al-qubh', or bad things, towards one's wife. The word 'al-qubhu' etymologically means the opposite of good or beautiful (hasan) and can be attributed to a physical description or action.